An ecological agency approach to understanding student absenteeism in a suburban, Kansas school - Kipp, Andrew L. (Kansas State University, 2022)
Student absenteeism is a persistent issue in education and is harmful to both the school and the absentee student. One approach to improving student absenteeism is targeting contextual factors within the learning environment. The study uniquely employs an ecological agency approach to understanding absenteeism within the suburban, Kansas school context. The ecological agency theoretical framework explores the person’s personal history, aspirations, and environmental conditions to better understand potential outlets or restrictions to their intended action. Using a case study methodology in a suburban, Kansas school context during the 2020-2021 school year, the study captures the decision-making of four high school absentee students using semi-structured interviews, drawings, and concept maps. The findings reveal that peer socialization opportunities, methods of instruction, shifts in cultural beliefs due to COVID-19, manifestations of anxiety and lack of space to escape their anxiety, social media bullying, and the inability to receive academic tutoring motivated the participants’ daily decision to either attend or miss school during the 2020-2021 school year. The findings provide a basis to improve several institutional and classroom practices. These practices include more student-led instruction and less teacher-led instruction in both in-person and remote learning environments, promoting socialization through classroom collaboration and clubs based on emerging student interests, reducing instances of bullying through prosocial education, safe spaces for students to escape the classroom to manage their anxiety, and more opportunities for one-on-one tutoring to improve grades. The study illustrates an example of using the ecological agency approach to better understand the personal and environmental factors that lead to absenteeism. The study also informs educational policy and classroom practice to better promote student attendance. Further research should investigate other school contexts using the ecological agency theoretical framework to better understand the influence of the school environment and personal contextual factors upon student absenteeism.
Keywords: Student absenteeism; Ecological agency; School improvement; Educational policy; Classroom practices; Student decision-making